2022
DOI: 10.3390/ijerph19084866
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Shielding Effect of Intergenerational Contact against Ageism in the Workplace: A Canadian Study

Abstract: Negative outcomes of ageism in the context of the Canadian labor market are well documented. Older workers remain the target of age-based stereotypes and attitudes on the part of employers. This study aims at assessing (1) the extent to which quality and quantity intergroup contacts between younger and older workers as well as knowledge-sharing practices reduce ageist attitudes, in turn (2) how a decrease in ageist attitudes increase the level of workers’ engagement and intentions to remain in the organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…More so, knowledge sharing practices between workers of different ages reinforce the perception of equal status, one of the conditions that maximizes the effects of intergroup contacts on prejudice (Choi & Jarrott, 2021). In Lagacé et al’s (2022) study, intergenerational knowledge sharing practices positively impacted both younger and older participants’ views about aging and older workers, which in turn, increased work engagement and intentions to remain in the organization.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…More so, knowledge sharing practices between workers of different ages reinforce the perception of equal status, one of the conditions that maximizes the effects of intergroup contacts on prejudice (Choi & Jarrott, 2021). In Lagacé et al’s (2022) study, intergenerational knowledge sharing practices positively impacted both younger and older participants’ views about aging and older workers, which in turn, increased work engagement and intentions to remain in the organization.…”
Section: Introductionmentioning
confidence: 84%
“…Taken together, findings from the Canadian and Belgian studies highlight that both younger and older workers may benefit from interacting and sharing knowledge with one another, as these can contribute to countering ageist stereotypes about older workers and in turn, increase work engagement as well as intentions to stay in the organization for workers of all ages (Iweins et al, 2013; Lagacé et al, 2022). However, these studies did not examine the extent to which the cognitive component of ageism (i.e., stereotypes) was associated with its behavioral component, namely, age-based discrimination (Solem, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also contributes to the literature on the intergroup contact tertiary effect, i.e., intergroup contact effects beyond intergroup relations [ 44 , 45 ]. Indeed, previous research has shown that intergroup contact can be associated for example with more pro-environmental behavior [ 46 ] or with organizational outcomes such as work engagement and reduced turnover intentions [ 47 ]. In this research we show that intergroup contact effects might also pertain to public health, being (indirectly via ageism) associated with attitudes toward the vaccination passport, see also [ 15 ].…”
Section: Discussionmentioning
confidence: 99%